MENINGKATKAN KEBERANIAN SISWA SMP KELAS VIII DALAM MENGEMUKAKAN PENDAPAT DALAM PEMBELAJARAN PAIBP DENGAN METODE TANYA JAWAB ATAU DISKUSI DI SMPIT BINA MASYARAKAT MANDIRI MEGAMENDUNG - Firmansyah Maulana Anugrah; Yal Robiansyah (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2023)
Religious Education is an important learning in the growth of student character, especially in an age of ease and moral decline that occurs everywhere.This study uses a class action research method conducted to improve the learning situation and improve the learning outcomes of SMPIT Bina Masyarakat Mandiri students. The learning model used is the discussion or question and answer learning model. With this learning model students can discuss, solve problems, and present the results of the discussion to be responded to by other students. This research was conducted in two cycles, in cycle 1 for the application of the method of discussion or question and answer presentations that reached a very developed value of 35 percent. In the cycle there was an increase to 80 percent. This shows that the application of this method in learning PAI BP to increase students' courage in expressing opinions, asking questions, answering and drawing conclusions is very effective.